PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP AFEKTIF RECEIVING DAN RESPONDING SISWA - Dira Tiara; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Universitas Lampung, 2014)
This research aimed to determine the effect of Talking Stick model in improving the afective of receiving and responding of the students at environmental pollution and waste material. The design was one-shot case study. The sample was class X1 selected by cluster random sampling. The research data was qualitative form. The qualitative data was obtained from the afective of receiving and responding percentage of the students by using Talking Stick model that was analyzed descriptively. The result showed that using Talking Stick model can improve the afective of receiving of the students with an average of 77.77% with good criteria and responding of the students with an average of 84.71% with good criteria. It was also showed from the increase of all aspects that was observed. Thus it can be concluded that using Talking Stick model in influence in increasing the afective of receiving and responding of the students. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Talking Stick terhadap afektif receiving dan responding siswa pada materi Pencemaran Lingkungan dan Limbah. Desain penelitian ini adalah one-shot case study. Sampel penelitian ini adalah kelas X1 yang dipilih secara cluster random sampling. Data penelitian ini berupa data kualitatif. Data kualitatif berupa rata-rata persentase afektif receiving dan responding siswa terhadap penggunaan model Talking Stick yang dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa penggunaan model Talking Stick dapat meningkatkan afektif receiving dengan rata-rata sebesar 77,77% dengan kriteria baik dan responding dengan rata-rata sebesar 84,71% dengan kriteria baik. Hal ini juga terlihat dari peningkatan untuk semua aspek yang di amati. Dengan demikian, dapat disimpulkan bahwa penggunaan model Talking Stick berpengaruh dalam meningkatkan afektif receiving dan responding siswa. Kata kunci : afektif receiving, afektif responding, pencemaran lingkungan dan limbah, talking stick